An empirical model for compressive strength of the limestone masonry based on number of courses – An experimental study. (20th October 2020) - Veríssimo-Anacleto, Jorge; Ludovico-Marques, Marco; Neto, Pedro
Highlights: Study of the uniaxial compression behaviour of limestone masonry. Characterization of the mechanical properties of the masonry materials used. Use of small-sized masonry specimens with different number of courses. An empirical model to predict the masonry compressive strength is proposed. Abstract: This experimental study aims to contribute to the knowledge of the mechanical behaviour of limestone masonry. In order to analyze the influence of varying the number of masonry courses on the behaviour of uniaxial compression, three series of small-size samples with different numbers of masonry courses are used. The characterization of the masonry materials (limestone prisms and mortar) are performed. The masonry specimens used are single-leaf regular ashlar masonry with joints made of natural hydraulic lime mortar and sand. The materials used in the experimental work are selected and manufactured to be representative of the mechanical characteristics present in old buildings, characterized by the quasi-homogeneity of stone blocks and low strength mortars. A new predictive model of the masonry compressive strength is herein presented that take into account the number of courses and the height of the masonry specimens. This model is evaluated by comparison with other existing models and shows a good agreement between the analytical and experimental values.